Coaching and mentoring - educational approach - Podgórska-Jachnik, Dorota; Adelbayeva, Nuriya; Gabdrakhmanova, Shynar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the recent years, coaching and mentoring have become popular methods of supporting personal development. They are willingly used, in particular, in management and business, but not only. Both methods are strongly associated with pedagogy as well as educational and philosophical re?ection on the transfer and personalized creation of individual resources of knowledge. The article discusses the basic assumptions of coaching and mentoring, as well as di?erences and similarities between them. This re?ection is important from the point of view of the need to enrich traditional education, both in and outside of school ? especially in the education and re-education of adults.
Keywords: coaching; mentoring; personal developments; individual resources of knowledge; rozwój osobisty; indywidualne zasoby wiedzy